Molecular scanning of candidate mitochondrial tRNA genes in type 2 (non-insulin dependent) diabetes mellitus. Issue 3 (March 1996) - Thomas, A W; Edwards, A; Sherratt, E J; Majid, A; Gagg, J; Alcolado, J C
Abstract : Mitochondrial DNA (mtDNA) gene defects may play a role in the development of non-insulin dependent diabetes mellitus (NIDDM). In order to search for potentially diabetogenic mtDNA defects we have applied the technique of single stranded conformational polymorphism (SSCP) analysis to 124 patients with a history of NIDDM and 40 non-diabetic controls. No new heteroplasmic mutations were detected. However, a variety of homoplasmic variants were found in patients with NIDDM; some of these merit further investigation.